2018
DOI: 10.1007/s11606-018-4656-7
|View full text |Cite
|
Sign up to set email alerts
|

Test Result Management Practices of Canadian Internal Medicine Physicians and Trainees

Abstract: BACKGROUND: Missed test results are a cause of medical error. Few studies have explored test result management in the inpatient setting. OBJECTIVE: To examine test result management practices of general internal medicine providers in the inpatient setting, examine satisfaction with practices, and quantify self-reported delays in result follow-up. DESIGN: Cross-sectional survey. PARTICIPANTS: General internal medicine attending physicians and trainees (residents and medical students) at three Canadian teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…For example, WAD has highlighted the uncertainty and variation in use of the of the results forwarding functionality for managing results that return after a patient has been admitted and the potential impact on electronic results notifications or communication with inpatient teams. Uncertainty also compelled clinicians to avoid using the functionality, or find alternatives, which concurs with the findings of Bodley et al, 17 who concluded, “If physicians are not taught how EHR functions can improve efficiency and patient safety, it seems logical that physicians would not use these functions....” Our findings therefore have implications for EMR training to ensure the scope of training not only covers how to use an application, but also addresses why functionality should be used, the benefits of use (including safety) and how the system processes information. Our findings add to existing literature in describing the challenges clinicians reported in using an electronic test results management application in an ED setting and take a step toward answering the call to “identify the problems” relating to HIT usability.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…For example, WAD has highlighted the uncertainty and variation in use of the of the results forwarding functionality for managing results that return after a patient has been admitted and the potential impact on electronic results notifications or communication with inpatient teams. Uncertainty also compelled clinicians to avoid using the functionality, or find alternatives, which concurs with the findings of Bodley et al, 17 who concluded, “If physicians are not taught how EHR functions can improve efficiency and patient safety, it seems logical that physicians would not use these functions....” Our findings therefore have implications for EMR training to ensure the scope of training not only covers how to use an application, but also addresses why functionality should be used, the benefits of use (including safety) and how the system processes information. Our findings add to existing literature in describing the challenges clinicians reported in using an electronic test results management application in an ED setting and take a step toward answering the call to “identify the problems” relating to HIT usability.…”
Section: Discussionsupporting
confidence: 76%
“…Despite the availability of an electronic test results management application, clinicians in the current study reported using a combination of both manual and electronic tracking strategies to ensure test results requiring follow-up were actioned (themes 1 and 5). This need to support “memory of pending tasks” 36 for managing test results and using paper-based strategies in HIT-enabled settings such as sticky notes, 17 , 35 lists, and logs, has been previously reported in the literature 17 , 18 , 35 , 36 and characterized as “workarounds.” 35 The paper and electronic tracking strategies we identified meet the definition of workarounds stated in Debono et al as “observed or described behaviors that may differ from organizationally prescribed or intended procedures.” 45 The context surrounding our participants’ adoption of workarounds are indicative of clinicians actively employing strategies to support the cognitive demands of tracking test results through to follow-up and completion. Thus, they also fall under the definition of resilience stated in Smith et al as “positive adaptability within systems that allows good outcomes in the presence of both favourable and adverse conditions.” 46 Although resilience strategies can maximize positive outcomes, they also risk obscuring underlying barriers or threats to safety.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although providing education and adequate supervision to resident physicians regarding the management of in-basket tasks was a primary goal of this study, the ultimate goal was to provide competent and efficient care to patients. A test is only useful if the results are reviewed and translated into action, not just lost in the electronic medical record [8]. It has already been noted that the lack of closed-loop communication with patients can lead to increased litigation, so, engaging the patient in their own care was of the utmost importance [3].…”
Section: Multi-faceted Approachmentioning
confidence: 99%